Analysis of silver coins from colonial Brazil by hand held XRF and micro-XRF. (December 2020) - Felix, Valter S.; Pereira, Marcelo O.; Freitas, Renato P.; Aranha, Paula J.M.; Heringer, Pedro C.S.; Anjos, Marcelino J.; Lopes, Ricardo T.
Abstract: In this work, 960 réis coins from the period when Brazil was a colony of Portugal were analyzed using the x-ray fluorescence (XRF) spectrometry. The history of these coins, dated between the end of the 17th century and the beginning of the 19th century, had a great influence on the immigration of the Portuguese Prince Regent D. João to Brazil, who arrived in 1808. Bearing in mind the need to expand the timid Brazilian monetary system, the Portuguese crown decided to collect Spanish silver pesos of 8 reales, recoined with a value of 960 réis . The recoinage procedure was carried out using a stamp; therefore, in many cases, it is possible to check the base currency. In this work, were investigated 17 samples of 960 réis coins by XRF, in which the base coin was 8 reales manufactured with raw materials from Mexican mines. In addition to characterizing the elemental composition of the coins, the XRF data were evaluated using multivariate statistical method of Robust Principal Component Analysis (ROBPCA), which was used to classify the coins based on their elemental composition. However, with XRF, elementary information is obtained for a depth of only a few micrometers. One of the essential issues in Ag–Cu metal alloys is the Ag enrichment, which can cause changes to the elemental composition of the surface. Therefore, initially, a study was carried out to verify whether the surface compositions of the coins were altered by the Ag enrichment. Graphical abstract: Image 1 Highlights: Analysis of Brazilian coins of 960 réis by XRF. Robust Principal Component Analysis (ROBPCA) applied to XRF data. Ag enrichment study by XRF.